Green Investment as a Guarantee to Protect the Indigenous People’s Rights - Listyani, Ajeng Aditya (Unifikasi : Jurnal Ilmu Hukum, 2024)
Investment opportunities are opened as widely as possible to achieve community welfare, including land use mechanisms. However, this endangers the existence of Indigenous People's rights. Indigenous people have limited access to their lives and livelihoods through land use. Therefore, measures are needed to ensure the protection of Indigenous People's rights in line with investment implementation. This research aimed to identify and analyse the concept of green investment and the implementation of green investment as an effort to ensure the protection of the rights of Indigenous People. This research was normative juridical research with a statutory approach and a concept approach. The data used was secondary data obtained from a literature study. The results showed that green investment focuses on how environmental balance is maintained amidst the implementation of investments. The concept of green investment in the land sector was realised by the division of land functions, the use of land in line with regional spatial plans, and the application of environmental insight in land use. In addition, the application of green investment could be a method to protect the rights of indigenous people and ensure the sustainability of economic growth.